Comunicação & encantamento: as histórias de fadas como mídia entre a realidade do mundo adulto e a realidade fantástica da criança - Dohme, Vania D´Angelo (2008)
The storytelling practice involves a whole system of sign and codes used in a similar way throughout the centuries, as the same meanings that are adequate to each period. This dissertation verses about the fairy tales and their tellers as mediators in the communication process among adults and children. It explores the several elements which compound this process and the influence that each one of them expresses to their quality, searching for means of potentials to the communication, optimizing the relationship and regarding the XXI century demanding. The research was of a bibliographic theoretical form aiming to create theoretical charts of references from several aspects of the studied questions in a profound manner and, subsequently, interconnected to provide a wider amplitude of the work object, putting down old paradigms and re-meaning some aspects. The first part was concerned with the story sender, understanding him as its author, seeking for revealing his communication intention considering authors as Bruno Bettelheim to pass through the stories as an existential and cognitive contribution to the children and Umberto Eco to understand them as a solution to the competence difference among the receiver, the child, and the sender, the author or the teller. The authors Baittelo and Flusser to characterize this communication as an attachment among its participants. Huizinga and Bystrina to pass through the reality occupied in the stories telling and Jung and Morin to analyze the arqueptical functions present in the stories. In order to understand a fairy tale structure it refers to Vladiir Propp and Greimas. The second chapter verses about the storytelling instrumentation, suggesting the necessary cautions for it to keep the cleanness of its message based on Jean Marie Gillig and in Stanislavski drama theories and of the primary media taught by Harry Pross. Chapter three reports the child as the process receptor making a Piaget s symbolical game with a cloth, the second reality of Bystrina and Huizinga s entertainment bubble to consider the stories beyond the oral transmission mean of a culture, a pedagogical mean of teaching and living. The fourth chapter studies Delors and Morin works ordered by Unesco to the XXI century education. We got to the conclusion that, since the stories refer to basic values for being and living in harmony, they continue being appropriate instruments for facing the complexity of the current days and future ones